2008
DOI: 10.1007/s10620-008-0299-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intracolonic Administration of Low-Molecular-Weight Heparin CB-01-05, Compared to Other Low-Molecular-Weight Heparins and Unfractionated Heparin, in Experimentally Induced Colitis in Rat

Abstract: Purpose Parenteral administration of lowmolecular-weight heparins (LMWHs) and unfractionated heparin (UFH) resulted effective in improving the symptoms of experimental colitis in rat. Today, there is little information about their activity by intracolonic instillation. The scope of this study was to evaluate the ability of CB-01-05 (a LMWH with a mean molecular weight of about 5,700), compared to a series of other LMWHs and to UFH, directly instilled into the distal colon of the rat, to ameliorate dinitrobenze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Previous in vivo 10 and in vitro 14 studies, and a pilot human trial 11 suggested a potential anti‐inflammatory effect of parnaparin sodium in the colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vivo 10 and in vitro 14 studies, and a pilot human trial 11 suggested a potential anti‐inflammatory effect of parnaparin sodium in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of evidence that LMWHs have been shown to be effective by oral administration, 9 this route has been considered inappropriate to treat UC because of the conviction that the LMWHs are quickly inactivated in the upper gastrointestinal tract therefore not reaching adequate concentrations in the colonic lumen. Recent observations proved that parnaparin sodium, an LMWH with a mean molecular mass around 5000, delivered by catheter into the colon of rat was highly effective in ameliorating dinitrobenzene (DNB)‐induced colitis 10 . This observation suggested that the administration of parnaparin sodium, contained in tablets delivering the product directly into the lumen of the colon, could represent a promising approach to treat UC.…”
Section: Introductionmentioning
confidence: 99%
“…Groups of 8-10 male Wistar rats (Charles River, Lecco, Italy) for a total of 27 animals weighing ~200-250 g were used. The test was performed as previously described (31), with the exception of a longer treatment duration. Colitis was induced in animals fasted overnight and under light ether anaesthesia, by instillation into the colonic lumen of 30 mg DNB dissolved in 0.25 ml ethanol 50%.…”
Section: Methodsmentioning
confidence: 99%
“…Data recently obtained using chemically induced colitis models suggest a potential role of two different LMWHs in ameliorating gut inflammation if administered directly on the epithelial surface. In one study, parnaparin, a LMWH of 5000 kD, was administered to rats intracolonically, and improved disease severity (156). In another study, colitic mice treated with microspheres loaded with enoxaparin (4500 kD), specifically designed to release the drug into the colon, resulted in a reduction of inflammatory activity after parenteral administration (157).…”
Section: Therapies That Enhance Intestinal Barrier Function In Ibdmentioning
confidence: 99%